2021
DOI: 10.1371/journal.pntd.0009275
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of single and mixed infections of Rift Valley fever virus, Brucella spp. and Coxiella burnetii in dromedary camels in Kenya

Abstract: Camels are increasingly becoming the livestock of choice for pastoralists reeling from effects of climate change in semi-arid and arid parts of Kenya. As the population of camels rises, better understanding of their role in the epidemiology of zoonotic diseases in Kenya is a public health priority. Rift Valley fever (RVF), brucellosis and Q fever are three of the top priority diseases in the country but the involvement of camels in the transmission dynamics of these diseases is poorly understood. We analyzed 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
(90 reference statements)
4
9
2
Order By: Relevance
“…The analysis of the possible risk factors of the disease showed no statistically signi cant association between the presence of antibodies to the virus and the sex of the camels. This is in contrast with the previous report by Muturi et al, (2021) that reported a signi cant association between infection and sex of camel in Kenya. This disparity may be due to differences in climatic zones and husbandry practices in the two study areas.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The analysis of the possible risk factors of the disease showed no statistically signi cant association between the presence of antibodies to the virus and the sex of the camels. This is in contrast with the previous report by Muturi et al, (2021) that reported a signi cant association between infection and sex of camel in Kenya. This disparity may be due to differences in climatic zones and husbandry practices in the two study areas.…”
Section: Discussioncontrasting
confidence: 99%
“…This disparity may be due to differences in climatic zones and husbandry practices in the two study areas. The study showed that age was a signi cant risk factor for the presence of antibodies and this agrees with previous reports from Kenya (Muturi et al, 2021) and Sudan (Abdallah et al, 2016). This may be because the older camels, having spent a long time in the environment might have been exposed to greater risk when compared to young (Abdallah et al, 2016;Selmi et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Camels are one of the major livestock animals important for agriculture and tourism in Kenya and could be a natural reservoir of viral pathogens [ 44 , 45 ]. Camel handlers, such as livestock farmers, traders, and butchers, may be at high risk of infectious diseases caused by camel-derived viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Co-infections of Q fever with other zoonotic agents such as Brucella spp. and Rift Valley fever virus (RVFV) are also common in animals; this could exacerbate the health outcomes of infected animals since these pathogens cause similar reproductive problems such as abortions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%